The Role of Molecular Allergens in the Diagnosis of Cat-Pork Syndrome: An Unusual Case Report - Barradas Lopes, Joana (2022)
Cat-pork syndrome is a rare condition, with few cases reported in the literature. This syndrome is justified by the homology between serum albumins from cat and pork. Evidence suggests that a primary sensitization to cat serum albumin Fel d 2 occurs, followed by allergic reactions after ingestion of pork meat containing serum albumin Sus s 1. Due to homology between other mammalian serum albumins, reactions with other meats can also be present. We report a well-documented case report of a patient with cat-pork syndrome, with initial mild and non-specific manifestations to well-cooked pork that were overlooked. Component resolved diagnosis was essential to establish the diagnosis, which confirmed the involvement of Fed 2 and Sus s 1, but less relevant in helping to define avoidance diets, since the sensitization profile was not in accordance with clinical manifestations.